Dopaminergic neuroprotective effects of rotigotine via 5-HT1A receptors: Possibly involvement of metallothionein expression in astrocytes. (January 2020) - Isooka, Nami; Miyazaki, Ikuko; Kikuoka, Ryo; Wada, Kouichi; Nakayama, Erika; Shin, Kotaro; Yamamoto, Daichi; Kitamura, Yoshihisa; Asanuma, Masato
Graphical abstract: Image 1 Abstract: Astrocytes exert neuroprotective effects through production of antioxidant molecules and neurotrophic factors. A recent study showed that stimulation of astrocyte serotonin 1A (5-HT1A) receptors promotes astrocyte proliferation and upregulation of the antioxidant molecules metallothionein (MT)-1, 2, which protect dopaminergic neurons against oxidative stress. Rotigotine, an anti-parkinsonian drug, can bind to dopamine and 5-HT1A receptors. In this study, we examined neuroprotective effects of rotigotine in models of Parkinson's disease and involvement of astrocyte 5-HT1A receptors in neuroprotective effects of rotigotine against dopaminergic neurodegeneration. Rotigotine increased the number of astrocytes and MT-1, 2 expression in cultured astrocytes. Pretreatment with conditioned media from rotigotine-treated astrocytes significantly inhibited 6-hydroxydopamine (6-OHDA)-induced dopaminergic neurotoxicity. These effects were completely blocked by a 5-HT1A antagonist or MT-1, 2 specific antibody. Subcutaneous administration of rotigotine increased MT-1, 2 expression in striatal astrocytes and prevented reduction of dopaminergic neurons in the substantia nigra of a 6-OHDA-lesioned mouse model of Parkinson's disease. These effects were blocked by co-administration with a 5-HT1A antagonist. These results suggest that rotigotine exerts neuroprotective effects through upregulation of MT expression in astrocytes by targeting 5-HT1A receptors. Our findings provide a possible therapeutic application of rotigotine to prevent dopaminergic neurodegeneration in Parkinson's disease. Highlights: Rotigotine upergulates metallothionein in astrocytes via 5-HT1A receptor. Rotigotine protects dopaminergic neurons by targeting astrocytic 5-HT1A receptor. Secreted astrocytic metallothionein by rotigotine protects dopaminergic neurons.